Recreational and rehabilitation aspects of psychological health and well-being of students: a systematic review - Lesia Korobeinikova; Tetiana Yermakova; Georgiy Korobeynikov; Daniil Vitenko (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Given the increasing attention to the psychological health and well-being of students, it is important to consider the impact of recreational and rehabilitation aspects. The purpose of this study is to analyze documents from the Web of Science (WoS) database from 2014 to 2024, focusing on the recreational and rehabilitation aspects of students' psychological health and well-being.